2021
DOI: 10.18632/aging.202889
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-202-3p in bone marrow mesenchymal stem cells improves cerebral ischemia-reperfusion injury by promoting angiogenesis and inhibiting inflammation

Abstract: Background: Cerebral ischemia-reperfusion injury (CIRI) can cause brain tissue inflammation, neuronal degeneration, and apoptosis. There is increasing evidence that microRNAs (miRNA) exert neuroprotective effects by regulating the inflammatory process during cerebral ischemia-reperfusion injury. Additionally, it is increasingly acknowledged that neuroinflammation is regulated by Toll-like receptor 4 (TLR4). However, it is unclear whether miRNA can exert its neuroprotective effects by regulating TLR4-mediated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Stem cell therapy is another promising treatment for IR-induced senescence. Multipotent mesenchymal stem cells (MSCs), being a category of adult stem cells springing from the mesoderm, with multi-directional differentiation and self-renewal potential, have recently emerged as a key player in regenerative medicine and clinical translational research [ 124 126 ]. Typically, MSCs have been extensively studied to inhibit premature senescence by protecting against the IR-induced pro-oxidative state, cell-cycle inhibition [ 93 ], and chronic fibrosis [ 127 ].…”
Section: Therapies That Target Cellular Senescence After Ir Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cell therapy is another promising treatment for IR-induced senescence. Multipotent mesenchymal stem cells (MSCs), being a category of adult stem cells springing from the mesoderm, with multi-directional differentiation and self-renewal potential, have recently emerged as a key player in regenerative medicine and clinical translational research [ 124 126 ]. Typically, MSCs have been extensively studied to inhibit premature senescence by protecting against the IR-induced pro-oxidative state, cell-cycle inhibition [ 93 ], and chronic fibrosis [ 127 ].…”
Section: Therapies That Target Cellular Senescence After Ir Injurymentioning
confidence: 99%
“…For instance, cell-cycle arrest of myocardiocytes after MI can be alleviated by MSC-EVs carrying miR-150-5p via downregulation of TXNIP [ 131 , 132 ], or by MSC-EVs targeting miR-497/Smad7/TGF-β pathway [ 133 ]. Yu et al also found that EVs carrying mi-202-3p could protect neurons from IR injury via downregulating TLR4-mediated inflammation response [ 124 ]. Xiao et al point that MSC-EVs reduce endothelial cell senescent burden and activate angiogenesis through miR-146a/Src pathway [ 134 ].…”
Section: Therapies That Target Cellular Senescence After Ir Injurymentioning
confidence: 99%
“…It has been reported that the transplantation of bone marrow mesenchymal stem cells (BMSCs) was able to induce the nerve function recovery after cerebral ischemia. 3 Additionally, a recent study indicated that BMSCs could alleviate the progression of CI/R injury through mediation of PI3K/Akt/mTOR signaling pathway. 4 More importantly, recent studies demonstrated that BMSCs-derived exosomes (BMSC-exos) were able to act as crucial mediators in the biological function of BMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…MiR - 202 - 3p is present in many human diseases and is a new potential biomarker for the diagnosis of type 1 gastric neuroendocrine tumors ( 11 ). Its overexpression in bone marrow mesenchymal stem cells improves cerebral ischemia-reperfusion injury by promoting angiogenesis and inhibiting inflammation ( 12 ). Additionally, the overexpression of nuclear-enriched autosomal transcript 1 promotes the proliferation, migration, and invasion of endometrial cancer cells and inhibits apoptosis by targeting the miRNA - 202 - 3p /T-cell immunoglobulin and mucin domain 4 axis ( 13 ).…”
Section: Introductionmentioning
confidence: 99%